PkM PENGEMBANGAN POS KESEHATAN PESANTREN (POSKESTREN) DI YAYASAN WAKAF UMI PESANTREN WIHDATUL ULUM DESA BONTOKASSI, KEC. PARANGLOE, KAB. GOWA TAHUN 2017 - Syam, Nasruddin; Gafur, Abd.; Hamzah, Wardiah (Jurnal BALIRESO, 2018)
Pesantren become motivator and innovator in health development, and become role model in cleanand healthy living behavior for the surrounding community. The problems of existing pesantrenincluding the partners (Yayasan Wakaf UMI Pesantren Wihdatul Ulum) in the service to thecommunity are: (1) Not knowing the condition and health condition of the surroundingcommunity, (2) Partners also do not have container of community empowerment in health sectorand, (3) Human resources that manage it. Self Awareness Survey showed that there are healthproblems of skin disease (itching and scabies), the issue of personal hygiene, sanitation or ,. Thenthe deliberation of poskestren formation and the election of board and cadre of poskestren (santrihusada) to run and run poskestren. In order for poskestren cadres to perform postcestrene activitiesthen conducted poskestren training that followed 30 people. In order poskestren activities can workwell it needs guidance specifically motivated cadre poskestren based health problems are advancedstudents and the community. The need for support of resources, such as table towels, beds andmedicine boxes in the secretariat poskestren